The BDNF-TrkB Pathway Acts Through Nucleus Accumbens D2 Expressing Neurons to Mediate Stress Susceptible Outcomes - Pagliusi, Marco; Franco, Daniela; Cole, Shannon; Morais-Silva, Gessynger [UNESP]; Chandra, Ramesh; Fox, Megan E.; Iñiguez, Sergio D.; Sartori, Cesar R.; Lobo, Mary Kay (Frontiers, 2022)
Brain-derived neurotrophic factor (BDNF) has a critical role in stress response including neuropsychiatric disorders that are precipitated by stress, such as major depressive disorder (MDD). BDNF acts through its full-length BDNF receptor tyrosine kinase B (TrkB) to trigger a pro-plasticity effect. In contrast, the truncated isoform of the BDNF receptor (TrkB.t1) triggers an anti-plasticity effect. In stress outcomes, BDNF acting in the hippocampus has a stress resilience effect, and, inversely, in the nucleus accumbens (NAc), BDNF acts as a stress susceptible molecule. It is unknown if BDNF-TrkB acts on a specific NAc projection neuron, i.e., medium spiny neuron (MSN or spiny projection neuron), a subtype in stress outcomes. To determine this, we performed chronic social or vicarious witness defeat stress (CSDS or CWDS) in mice expressing TrkB.t1 in dopamine receptor 1 or 2 containing MSNs (D1- or D2-MSNs). Our results showed that TrkB.t1 overexpression in NAc D2-MSNs prevented the CSDS-induced social avoidance or other stress susceptible behaviors in male and female mice. We further showed that this overexpression in D2-MSNs blocked stress susceptible behavior induced by intra-NAc BDNF infusion. In contrast, our results demonstrate that overexpression of TrkB.t1 on NAc D1-MSNs facilitates the SDS susceptible behaviors. Our study provides enhanced details into the NAc cell subtype role of BDNF-TrkB signaling in stress outcomes.
Keywords: depression; medium spiny neurons; nucleus accumbens (NAc); resilience; social defeat stress; witness defeat